Persoalan Lingkungan Hidup dalam UU Cipta Kerja dan Arah Perbaikannya Pasca Putusan MK Nomor 91/PUU-XVIII/2020 - Hamdani, Fathul; Fauzia, Ana; Maha Putra, Eduard Awang; Walini, Eno Liska; Pambudi, Bagus Ageng; Akbariman, Lalu Nahudatu (Indonesia Berdaya, 2022)
One the things in the Law Number 11 year of 2020 about Job Creation that cause problem is the deletion of an article concerning Environmental Permit Obligations. Environmental Permit Obligation is not strictly regulated in the Law of Job Creation. However, a petitioner must get a ruling about Environmental Eligibility to be permitted in running a business. Environmental Permission’s Nomenclature and Substance in Law of Environmental Protection and Management is changed into Environmental Agreement in the Law of Job Creation. The purpose of writing this article is to analyze environmental disputes in the Law of Job Creation, analyze environmental issue connected to Human Right, and also suggest improvement concerning environmental provision after the constitutional court’s decision number 91/PUU-XVIII/2020. The result of the research indicate that in order for a legal product that is born to be functional in the order of life of the nation and state, the legal product must accommodate what is the soul of the nation, which must be in accordance with and in harmony with the values contained in the Constitution. In addition, the right to the environment is one of the human rights regulated by the constitution, so that the revision of the Job Creation Law after the Constitutional Court’s decision related to the environment must prioritize human rights and sustainable development, especially by accommodating related environmental permit obligations in the form of Environmental Impact Assessment. Abstrak: Salah satu hal di dalam Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja (UU Cipta Kerja) yang memunculkan persoalan adalah dihapusnya pasal mengenai kewajiban izin lingkungan. Dalam UU Cipta Kerja, izin lingkungan tidak diatur secara tegas. Namun, untuk mendapatkan izin berusaha, pemohon harus mendapatkan keputusan mengenai kelayakan lingkungan. Izin Lingkungan dalam UU PPLH diubah nomenklatur dan substansinya menjadi persetujuan lingkungan dalam UU Cipta Kerja. Tujuan dari penulisan artikel ini adalah untuk mengkaji permasalahan lingkungan hidup dalam UU Cipta Kerja, mengkaji isu lingkungan hidup dalam kaitannya dengan hak asasi manusia, serta memberikan saran perbaikan mengenai ketentuan lingkungan hidup pasca Putusan MK Nomor 91/PUU-XVIII/2020. Hasil penelitian menunjukkan bahwa agar suatu produk hukum yang dilahirkan menjadi fungsional dalam tatanan kehidupan berbangsa dan bernegara, maka produk hukum tersebut harus mengakomodir apa yang menjadi jiwa bangsa, yakni harus sesuai dan selaras dengan nilai-nilai yang terkandung dalam Konstitusi. Selain itu , hak atas lingkungan hidup adalah salah satu hak asasi yang diatur oleh Konstitusi, sehingga revisi UU Cipta Kerja pasca putusan MK terkait lingkungan hidup harus mengedepankan hak asasi manusia dan pembangunan yang berkelanjutan, khususnya dengan mengakomodir terkait kewajiban izin lingkungan berupa Amdal.